Evaluation of a Serum Formulation Containing Durian (Durio zibethinus Murray) Peel Extract Against Propionibacterium acnes - Arief Azis; A Muh Fadjri (Akademi Farmasi Yamasi Makassar, 2026)
Durian fruit peel (Durio zibethinus Murray) contains active compounds, namely, flavonoids, tannins, saponins, and phenolics which are antibacterial and antioxidant so that it can be used as an alternative active ingredient for facial skin care. This study aims to determine whether the serum preparation of durian fruit peel extract (Durio zibethinus Murray) has an antibacterial effect on Propionibacterium acnes with concentrations of 10%, 15% and 20%. This study aims to determine whether the Serum Preparation Test of Durian Fruit Peel Extract (Durio zibethinus Murray) Against Propionibacterium acnes has an antibacterial effect made in the preparation of serum extract with a concentration of 10%, 15%, 20%. This test uses a laboratory experimental method carried out at the Microbiology Laboratory of the Yamasi Academy of Pharmacy Makassar, then testing the antibacterial activity of Durian Fruit Peel Extract Serum (Durio zibethinus Murray) with the well method and Medium agar (NA) as media and incubated for 1 x 24 hours at 37oC. Then observations were made by measuring the inhibition zone that occurred at each concentration of the preparation on Propionibacterium acnes test bacteria. The inhibition zone of 10% concentration showed a diameter of 9.5 mm, 15% concentration showed a diameter of 12.2 mm, and 20% concentration showed an inhibition zone of 14.9 mm with the results of inhibiting bacterial growth categorized as strong (10-19mm). The conclusion of the study states that the serum preparation of durian fruit peel extract (Durio zibethinus Murray) with a concentration of 15% and 20% is better and stronger than the concentration of 10%.